Biomarkers to evaluate the effects of temperature and methanol on recombinant Pichia pastoris - Zepeda, Andrea B. (2014)
Pichia pastoris is methylotrophic yeast used as an efficient expression system for heterologous protein production. In order to evaluate the effects of temperature (10 and 30 °C) and methanol (1 and 3% (v/v)) on genetically-modified Pichia pastoris, different biomarkers were evaluated: Heat stress (HSF-1 and Hsp70), oxidative stress (OGG1 and TBARS) and antioxidant (GLR). Three yeast cultures were performed: 3X = 3% methanol-10 °C, 4X = 3% methanol-30 °C, and 5X = 1% methanol-10°C. The expression level of HIF-1α, HSF-1, HSP-70 and HSP-90 biomarkers were measured by Western blot and in situ detection was performed by immunocytochemistry. Ours results show that at 3% methanol -30 °C there is an increase of mitochondrial OGG1 (mtOGG1), Glutathione Reductase (GLR) and TBARS. In addition, there was a cytosolic expression of HSF-1 and HSP-70, which indicates a deprotection against nucleolar fragmentation (apoptosis). On the other hand, at 3% methanol -10 °C and 1% and at methanol -10 °C conditions there was nuclear expression of OGG1, lower levels of TBARS and lower expression of GLR, cytosolic expression of HSF-1 and nuclear expression HSP-70. In conclusion, our results suggest that 3% methanol-30 °C is a condition that induces a strong oxidative stress and risk factors of apoptosis in modified-genetically P. pastoris.